2018
DOI: 10.1177/0391398818793088
|View full text |Cite
|
Sign up to set email alerts
|

Sex-age-specific handgrip strength and mortality in an incident hemodialysis cohort: The risk explained by nutrition and comorbidities

Abstract: These results provide support for the assessment of handgrip strength in all maintenance hemodialysis patients for early identification of those who may require special care to improve nutritional status and survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 33 publications
1
9
0
2
Order By: Relevance
“…21 In an incident hemodialysis cohort, HGS was found to be associated with mortality in a sex-, and age-specific manner. 22 The discrepancies in the association between HGS and MCI may be owing to sex and/or age effects; however, such detailed patient information is not currently available.…”
Section: Introductionmentioning
confidence: 99%
“…21 In an incident hemodialysis cohort, HGS was found to be associated with mortality in a sex-, and age-specific manner. 22 The discrepancies in the association between HGS and MCI may be owing to sex and/or age effects; however, such detailed patient information is not currently available.…”
Section: Introductionmentioning
confidence: 99%
“…In summary, the difference of muscle strength between the sexes is already well known. Moreover, recent studies have proved that different races and ages are associated with different cut-off values [3,12,22,24,25].…”
Section: Discussionmentioning
confidence: 99%
“…This study showed an independent association between HGS and all-cause mortality in both men and women, even after adjustment for both CRP and albumin. Other similar studies did not correct for these two indicators at the same time (12)(13)(14)(15)(16)(17)(18). In addition, compared to other studies with non-Asian MHD patients, we analyzed the association between all-cause mortality and HGS with both categories and continuous values of HGS.…”
Section: Discussionmentioning
confidence: 99%
“…It seems to not be influenced by hydration status like other methods for lean body mass evaluation (7,(9)(10)(11). So far, several studies have reported a negative relationship between HGS and mortality risk mainly in non-Asian hemodialysis patients (12)(13)(14)(15)(16). However, some studies failed to show a statistically significant association between HGS and all-cause mortality (17, Copyright © 2019, Author(s).…”
Section: Introductionmentioning
confidence: 99%